KONTRIBUSI PELAKSANAAN SUPERVISI TERHADAP MOTIVASI KERJA GURU DI SMP NEGERI TILANTANG KAMANG AGAM - Eni Desfitri (Ensiklopedia of Journal, 2023)
This study aims to explain the Contribution of the Implementation of Supervision to Teacher Work Motivation in Public Middle Schools, Tilantang Kamang District, Agam Regency. The method used in this study is a quantitative research method with the type of ex post facto research which will describe the Contribution of Supervision Implementation to Teacher Work Motivation at Public Junior High Schools, Tilantang Kamang District, Agam Regency. This population involved 52 samples from a total population of 113 people, using a stratified proportional random sampling technique with level of education and years of service. Data collection techniques used questionnaires, and were analyzed using correlation and regression statistical techniques. The results of data processing and analysis show that the implementation of supervision contributes significantly (21.2%) with a 99% confidence level, which is significant for teachers' work motivation. And it can be concluded that the Implementation of Supervision affects the work motivation of State Middle School Teachers, Tilantang Kamang District, Agam Regency.Keywords: Implementation of Supervision, Teachers, Teacher Work Motivation